Adding Far-Red to Red-Blue Light-Emitting Diode Light Promotes Yield of Lettuce at Different Planting Densities - Jin, Wenqing; Urbina, Jorge Leigh; Heuvelink, Ep; Marcelis, Leo F. M. (Frontiers in Plant Science, 2021)
The economic viability and energy use of vertical farms strongly depend on the efficiency of the use of light. Increasing far-red radiation (FR, 700-800 nm) relative to photosynthetically active radiation (PAR, 400-700 nm) may induce shade avoidance responses including stem elongation and leaf expansion which would benefit light interception and FR might even be photosynthetic active when used in combination with PAR. The aim of this study is to investigate the interaction between FR and planting density and to quantify the underlying components of the FR effects on growth. Lettuce (Lactuca sativa cv. Expertise RZ) was grown in a climate chamber under two FR treatments (0 or 52 µmol·m-2·s-1) and three planting densities (23, 37, 51 plants·m-2). Photosynthetically active radiation (PAR) of 89% red and 11% blue was kept at 218 µmol m-2 s-1. Adding FR increased plant dry weight after 4 weeks by 46%-77% (largest effect at lowest planting density) and leaf area by 58%-75% (largest effect at middle planting density). Radiation use efficiency (RUE: plant dry weight per unit of incident radiation, 400-800nm) increased by 17%-42% and incident light use efficiency (LUEinc: plant dry weight per unit of incident PAR, 400-700nm) increased by 46%-77% by adding FR; the largest FR effects were observed at the lowest planting density. Intercepted light use efficiency (LUEint: plant dry weight per unit of intercepted PAR) increased by FR(8%-23%). Neither specific leaf area nor net leaf photosynthetic rate was influenced by FR. We conclude that supplemental FR increased plant biomass production mainly by faster leaf area expansion, which increased light interception. The effects of FR on plant dry weight are stronger at low than at high planting density. Additionally, an increased LUEint may contribute to the increased biomass production.